Inhibition of the Wnt palmitoyltransferase porcupine suppresses cell growth and downregulates the Wnt/β-catenin pathway in gastric cancer - MO, MIN-LI (D.A. Spandidos, 2013)
Similarly to the Wnt protein palmitoyltransferase, porcupine (PPN) is essential to the activation of the Wnt/β-catenin signaling pathway. However, little is known about the role of PPN activity in human gastric cancer, one of the most common causes of cancer-related mortality. Real-time quantitative PCR was used to detect the expression levels of PPN in paired gastric cancer tissues. Cell proliferation, migration and invasion assays were performed following treatment using a newly developed small molecule PPN inhibitor (inhibitors of Wnt production, IWP-2) in the gastric cancer MKN28 cell line. Expression of downstream target genes and transcriptional activity of the Wnt/β-catenin signaling pathway were examined following IWP-2 treatment in MKN28. We identified that PPN was overexpressed in human gastric cancer tissue samples and cell lines. Following treatment of the gastric cancer cell line MKN28 with IWP-2, we detected that IWP-2 decreased MKN28 cell proliferation, migration and invasion, and elevated caspase 3/7 activity. Further analysis demonstrated that IWP-2 downregulated the transcriptional activity of the Wnt/β-catenin signaling pathway and downregulated the expression levels of downstream Wnt/β-catenin target genes in MKN28 cells. As current Wnt pathway-targeting strategies used for anticancer therapy have mainly focused on Wnt-receiving cells, our data shed light on the potential use of Wnt palmitoyltransferase PPN inhibitors to abrogate Wnt production in Wnt-producing cells, thus providing a potential therapeutic option for gastric cancer.